2001
DOI: 10.1023/a:1011169332265
|View full text |Cite
|
Sign up to set email alerts
|

Positron emission tomography (PET) with 18F-fluorodeoxyglucose (18F-FDG) for the staging of low-grade non-Hodgkin’s lymphoma (NHL)

Abstract: PET may contribute to the management of patients with low-grade follicular NHL. For the other low-grade lymphoma subtypes, the role of PET is less evident. Further studies using PET to evaluate the results of treatment or to diagnose disease recurrence are warranted in low-grade follicular NHL.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
118
1
11

Year Published

2003
2003
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 257 publications
(134 citation statements)
references
References 26 publications
4
118
1
11
Order By: Relevance
“…No abnormal tracer uptake was seen in the patient with low-grade gastric NHL of the MALT type, they found more tumor extension compared to endoscopy but they didn't report the CT finding. Jerusalem et al reported that PET plus a bone marrow biopsy compared to conventional staging procedures (also including a bone marrow biopsy) observed the same stage in 37 patients, a higher stage by PET in two patients [12], in our study PET detected bone marrow disease in 16 patients could not be catched by CT scan alone, and this was confirmed by bone marrow biopsy results, taking into consideration that the Jerusalem series was for patients with low grade lesions. Diffuse high FDG uptake of the bone marrow can occur due to the reactive changes of chemotherapy or the use of Colony-stimulating Growth factors (CSGF), in our study we insisted that the patient do not receive chemotherapy or CSGF at least two weeks prior to their PET scan.…”
Section: Discussionsupporting
confidence: 85%
“…No abnormal tracer uptake was seen in the patient with low-grade gastric NHL of the MALT type, they found more tumor extension compared to endoscopy but they didn't report the CT finding. Jerusalem et al reported that PET plus a bone marrow biopsy compared to conventional staging procedures (also including a bone marrow biopsy) observed the same stage in 37 patients, a higher stage by PET in two patients [12], in our study PET detected bone marrow disease in 16 patients could not be catched by CT scan alone, and this was confirmed by bone marrow biopsy results, taking into consideration that the Jerusalem series was for patients with low grade lesions. Diffuse high FDG uptake of the bone marrow can occur due to the reactive changes of chemotherapy or the use of Colony-stimulating Growth factors (CSGF), in our study we insisted that the patient do not receive chemotherapy or CSGF at least two weeks prior to their PET scan.…”
Section: Discussionsupporting
confidence: 85%
“…sification, indolent lymphomas frequently lack FDG avidity. 19 However, their incidence might increase in the future due to improved patient survival and given the higher age of transplant recipients. 20 Secondly, PET scan is not the preferred examination in case of suspicion of central nervous system localization.…”
Section: Ptldmentioning
confidence: 99%
“…Combined FDG-PET/CT has also been shown to be more accurate than PET alone or CT alone in the staging, restaging of patients with indolent lymphomas [13,15,16]. To our knowledge, to date, no study has investigated the value of FDG-PET specifically in the patient population of WM.…”
Section: Introductionmentioning
confidence: 99%